Historical Aspects in Sociological Studies and Implications for the Study of Sociology in the Academic World - David Manoel Armindo (Global Writing Academica Researching & Publishing, 2023)
This article has as a central focus the chair of sociology, aiming to expose the historical traces of its institutionalization in the secondary studies of Sergipe, since its first signs, in 1892, when it was created under the name of “sociologia, moral, noções de economia política e direito pátrio” (sociology, moral, notions of political economy and national law), until 1925, when it became an autonomous chair. The documental sources used were primarily legislative texts, as well as documents produced by the Atheneu Sergipense. Sociology emphasizes the importance of social networks and relationships in shaping historical outcomes. Social networks can influence everything from economic success to political power to health outcomes. For example, a person's social connections can impact their ability to find a job or access healthcare, and can also influence their political views and behaviors.